Synergistic targeted inhibition of MEK and dual PI3K/mTOR diminishes viability and inhibits tumor growth of canine melanoma underscoring its utility as a preclinical model for human mucosal melanoma. (22nd September 2016) - Wei, Bih‐Rong; Michael, Helen T.; Halsey, Charles H.C.; Peer, Cody J.; Adhikari, Amit; Dwyer, Jennifer E.; Hoover, Shelley B.; El Meskini, Rajaa; Kozlov, Serguei; Weaver Ohler, Zoe; Figg, William. D.; Merlino, Glenn; et al.
Summary: Human mucosal melanoma (MM), an uncommon, aggressive and diverse subtype, shares characteristics with spontaneous MM in dogs. Although BRAF and N‐RAS mutations are uncommon in MM in both species, the majority of human and canine MM evaluated exhibited RAS/ERK and/or PI3K/mTOR signaling pathway activation. Canine MM cell lines, with varying ERK and AKT/mTOR activation levels reflective of naturally occurring differences in dogs, were sensitive to the MEK inhibitor GSK1120212 and dual PI3K/mTOR inhibitor NVP‐BEZ235. The two‐drug combination synergistically decreased cell survival in association with caspase 3/7 activation, as well as altered expression of cell cycle regulatory proteins and Bcl‐2 family proteins. In combination, the two drugs targeted their respective signaling pathways, potentiating reduction of pathway mediators p‐ERK, p‐AKT, p‐S6, and 4E‐BP1 in vitro, and in association with significantly inhibited solid tumor growth in MM xenografts in mice. These findings provide evidence of synergistic therapeutic efficacy when simultaneously targeting multiple mediators in melanoma with Ras/ERK and PI3K/mTOR pathway activation.